Reading Myanmar's inland fisheries: postcolonial literature as theoretical lens. Issue 1 (2nd January 2019) - Campbell, Stephen
ABSTRACT: Interdisciplinary in scope, this article takes up the 1950 short story, "Ko Danga, " by Burmese author Kyay Ni, as a critical lens through which to approach the contemporary political economy of Myanmar's inland fisheries. Due to its level of ethnographic detail, Kyay Ni's account of the inland fisheries regime in early postcolonial Burma provides an effective historic baseline against which to assess more recent developments in this sector – developments outlined herein based on interviews and research trips to inland fishery locations in Myanmar's Ayeyarwady Region. Going further, the article argues that Kyay Ni's writing offers heterodox insights into contemporary political economic concerns, of relevance in Myanmar and more broadly.